Evaluasi Program Pembelajaran Tahsin Al-Qur’an Melalui Tutor Sebaya di Pondok Pesantren Putri Ummul Mukminin Berdasarkan Model Cipp - Musfirah, Nurul; N, Nurbaya; Rasyid, Muhammad Nur Akbar; N, Nursalam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to evaluate a tahsin coaching program through peer tutors in Ummul Mukminin Girls Boarding House using the CIPP (Context, Input, Process, Product) evaluation model. The study used a qualitative approach with an evaluation design that included analysis of the program context, inputs used, implementation processes, and outcomes achieved. The data source involved participants from Ummul Mukminin Girls Boarding School lodge. Data were collected through interviews, document analysis, and observation. The data analysis techniques used were data reduction, data presentation, and inference drawing. The results of the evaluation of the Qur’anic tahsin program through peer tutors in Ummul Mukminin Girls Boarding House were judged to be relevant and beneficial in improving the Qur’anic reading ability of students. Optimization of inputs and processes is required to achieve more maximized results. On the contextual aspect of the Qur’anic tahsin program through peer tutors is needed to answer the low Qur’anic reading ability of students coming from diverse religious educational backgrounds. The peer tutor approach was chosen because it is capable of creating a comfortable and effective learning atmosphere, as well as helping with teaching staff constraints. The resource input aspects of the tahsin program include teachers, peer tutors, Iqra’ books, and relatively adequate study rooms. Process aspects The implementation of the tahsin program goes with the peer tutor method which effectively builds interaction and learning convenience. Lastly, the product aspect will present the learners’ learning outcomes. Discussion will relate findings to related literature and theory, as well as relevant prior research.